Helix Model in Tourism Development Based on Sustainable Tourism Development in the Nongkosawit Tourism Village, Semarang City - Rizki Hidayati; Tri Yuniningsih; Endang Larasati S (PERSPEKTIF, 2023)
This article aims to analyze the helix model in tourism development in the Nongkosawit Tourism Village. The problem is focused on sustainable tourism development, identification of stakeholders involved, and the model. To approach this problem, theoretical references from Cooper, Swarbrooke, Maryono, and Sturesson, E., Lindmark, A., & Nilsson Roos, M. Data collection was carried out through document review, interviews, and observations. The technique for determining informants uses the snowball technique. The results of this research show that the development of sustainable tourism in the Nongkosawit Tourism Village, analyzed from an economic aspect, has not provided maximum benefits, so from a social and cultural aspect it can be said to be quite optimal, and from an environmental aspect quite optimal. The results of the field findings show that sustainable tourism development in the Nongkosawit Tourism Village has not implemented the principles of sustainable tourism. The stakeholders involved in tourism development in the Nongkosawit Tourism Village are grouped into three, namely primary, secondary, and key stakeholders which then form the Penta helix model. There are several supporting factors and factors that are considered to be obstacles to developing tourism in the Nongkosawit Tourism Village.